Modernisasi Pendidikan Islam Indonesia (Analisis Kritis Perkembangan pada Aspek Kurikulum dan Sumber Daya Manusia) - Media Gusman (STAI Serdang Lubuk Pakam, 2021)
This study aims to analyze the modernization of Islamic education in the curriculum and Human Resource aspects of Madrasahs. The focus of the discussion is more on the historicity and development. This research is a library research (Library Study), where the data sources used are books, or research journals related to the modernization of education in the curriculum and human resources aspects of Madrasahs. Data collection is of course done with documentation techniques. Namely tracing all library documents such as books, research reports, research journals, and so on. For data analysis, the researcher used content analysis techniques, meaning that the data obtained from various sources were then analyzed for the material to be drawn conclusions. The results of the research show that the existing reforms have greatly enlightened the name of the madrasa in the midst of the life of the Indonesian people. If in the past, madrasas were marginalized by the colonialists, now madrasas are included in the body of the National education system. Madrasas are institutions whose existence is equivalent to general education. From the aspect of human resources, madrasas have also developed, both in terms of qualifications and competence.